Bank Distress in Nigeria and the Nigeria Deposit Insurance Corporation Intervention (Global Journal of Management and Business Research, 2013)
The Banking Sector has been relied upon by many household, small savers and industrialists to provide their financial assistance at one time or the other. While it is expected that they do this very well, banks have fallen short-off expectations in this respect due to fraud, mismanagement, inexperience and the initial absence of regulatory laws and authorities. People lost their trust and confidence in the banking system, which the government couldn't afford. The government desirous to instill confidence on the banking system by the public put the Nigeria Deposit Insurance Corporation (NDIC) in place. The objective of this project work is to see how the NDIC through its various activities have been able to restore confidence in the banking system. Secondary data were primarily used for this work because of the peculiar nature of the research work. Correlation coefficient and r-test were used to test the relationship between the variables. It was discovered that due to the increase in deposit guarantee, there is an increase in deposit mobilization. It was also discovered that the NDIC has transmitted from the flat rate premium assessment system to a differential premium assessment system. It is therefore recommended that from time to time, the deposit cover should be reviewed in conformity with the happenings in the economy.
Keywords: bank failure; deposit guarantee; supervision; liquidation; public confidence; regulatory authorities